2021
DOI: 10.1186/s12879-021-06631-5
|View full text |Cite
|
Sign up to set email alerts
|

Imported leishmaniasis in travelers: a 7-year retrospective from a Parisian hospital in France

Abstract: Background Leishmaniases are regularly seen in non-endemic areas due to the increase of international travels. They include cutaneous leishmaniases (CL) and mucocutaneous (MC) caused by different Leishmania species, and visceral leishmaniases (VL) which present with non-specific symptoms. Methods We reviewed all consecutive leishmaniasis cases seen between September 2012 and May 2020. The diagnostic strategy included microscopy after May-Grünwald-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…In our study, we found 21 pediatric CL cases in Eskişehir, which were not endemic leishmaniasis. This, in parallel with the recent literature, supports that the frequency of CL cases has increased in non-endemic regions after wars and migrations (11,12).…”
Section: Discussionsupporting
confidence: 86%
“…In our study, we found 21 pediatric CL cases in Eskişehir, which were not endemic leishmaniasis. This, in parallel with the recent literature, supports that the frequency of CL cases has increased in non-endemic regions after wars and migrations (11,12).…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, case notification may vary within countries, judging by the marked differences in HumL incidence in some close by regions. There was evidence for increasing incidence of CL in later years, which is in line with rising rates of migration from and travelling of Europeans to endemic countries [ 155 , 156 ]. This typically benign clinical form is often treated at primary health centers and private clinics and may indeed be extensively underreported [ 157 ].…”
Section: Discussionmentioning
confidence: 98%
“…Most cases are reported in Brazil, India, Somalia, Sudan, Ethiopia, and Kenya,5 but cases are also increasing in non-endemic regions23 for reasons including refugee travel from endemic countries; the breakdown of health, housing, and sanitation infrastructure due to global unrest23; and climate changes, including rising temperatures and humidity, which promote increases in sandfly numbers. Increasing international travel also leads to leishmaniasis being increasingly reported in travellers returning to non-endemic countries 13. For example, in a statistical analysis of the serum and risk factor data of 200 US soldiers who travelled to Iraq between 2002 and 2011, the prevalence of asymptomatic visceral leishmaniasis (positive laboratory test result but absent clinical manifestations) was 19.5% 14.…”
Section: What Is the Epidemiology?mentioning
confidence: 99%